What we can learn from U.S. food policy response to crises of the last 20 years – Lessons for the COVID-19 era: A scoping review. (March 2022) - Fraser, Katherine Tomaino; Shapiro, Sarah; Willingham, Craig; Tavarez, Emilio; Berg, Joel; Freudenberg, Nicholas
Abstract: The U.S government has historically responded to human, natural and economic disruptions that threaten food insecurity by modifying federally-funded public food programs. The authors conducted a scoping review to identify and summarize available evidence on the efforts of a 20-year period to modify food benefit programs in response to emergencies; describe how food benefit programs interact to support vulnerable populations; identify key facilitators and barriers to effective implementation and impact; and assess relevance of evidence to COVID-19 pandemic. Scoping reviews address broad research questions aimed at mapping key concepts and available evidence in a defined area, and include academic and gray literature and reports from governments and NGOs. This review followed the PRISMA Extension for Scoping Reviews and included a three-stage search strategy. Studies were independently screened for eligibility by two researchers with multiple rounds of review. A content based charting method was used to summarize evidence. More than 2289 documents were identified and screened. After review, 44 documents were analyzed. Only 18% of documents reported program or policy impact data. Additionally, review of 149 policy records from State by State FNS Disaster Assistance Data from Oct 2016–Dec 2020 assessed 96 state specific food policy responses to 72 distinct events. Analysis revealed 53 distinct packages of food policy modifications used in response to crises. This scoping review demonstrates that few studies document the impact on food insecurity of food benefit modifications in response to crises. Most documents present output level details about costs and total number of individuals served. Many documents describe food policy response to crises without providing evaluation of response. Analysis points to SNAP and Child Nutrition Programs as most commonly modified food benefit programs in the wake of U.S. crises. The review concludes with a number of considerations for continued response to the ongoing COVID-19 crisis. Highlights: Few studies document food security impact of food benefit modifications in response to crises. Instead, most studies document food policy modifications, their economic costs, and reach. SNAP and Child Nutrition Programs are most commonly modified food benefits in wake of U.S. crises. Large scale complex crisis that threaten food security require multipronged food policy response. There is more the federal government can do to limit COVID-19's impact on food insecurity and hunger.